La guerre franco-allemande 1870-1871 - Jaurès, Jean; Duroselle, Jean-Baptiste; Rebérioux, Madeleine (Paris : Flammarion, 1971)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Frans-Duitse Oorlog